Prarancangan Pabrik Polistiren dari Stiren Monomer dengan Kapasitas 60.000 Ton/Tahun - , KEVIN CLEARY WANTA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Preliminary plant design of polystyrene manufacturing from styrene monomer studies its feasibility to produce general purpose polystyrene (GPPS) with production capacity of 60,000 tons/year. The plant continuously operates in 330 days a year and 24 hours a day. In this solution polymerization process, styrene monomer is needed as main raw material at rate of 87,044.36 tons/year, and ethyl benzene and benzoyl peroxide are needed as supporting raw material at rate of 5.70 tons/year and 140.50 tons/year. Raw material is processed in the continuous stirred tank reactor that is operated under condition atmospheric pressure and 90oC temperature. The plant is planned to be established at industrial area in Cilegon, Banten with 11,500 sqm area. It is supposed to employ about 188 workers. This plant utilizes water from Cidanau river at rate of 11,887.66 kg/hour before is processed in utility section. Two thousand four hundred and fifty five kilowatts of electricity is supplied by generator set. This plant also has steam reforming section, instrument air section, and waste water treatment section. Fixed capital of US$ 12,405,503.54 + IDR 70.241.840.874,41 and working capital of US$ 27,757,580.48are needed to establish the plant. It provides IDR 89.314.843.092,48 as profit before tax or IDR 44.657.421.546,24 as profit after tax. Based on economic analysis, Return of Investment (ROI) is 42.33% before tax or 21.17% after tax. Pay Out Time (POT) is 1.91 years before tax or 3,21 years after tax. Break Even Point (BEP) is 51.67% and Shut Down Point (SDP) is 38.88%. Discounted Cash Flow Rate of Return (DCFRR) is 27.07% per year. Therefore, further research in polystyrene plant for styrene monomer with production capacity of 60,000 tons/year should be carried out.